Assessment of farmers' view on the current use of manure around Holetta Agric.Res. Center - Kumsa, T.; Madsen, J.O.; Tegegne, Azage (Ethiopian Society of Animal Production, 2004)
A survey study was conducted in 'a mixed crop/livestock production system in the central highlands of Ethiopia around Holetta Research Center in the year 2000. The main purposes of the study were to understand the reasons behind the burning of manure by farmers instead of employing it all to solve the serious soil fertility problems they are confronted with and to examine other uses of animal dung if any. Results from this study showed that farmers owning cattle invariably produce dung cake for the provision of energy for cooking, lighting and heating utilities. Each household on average produces 1185.1 t 41.28 pieces of dung cake weighing 0.96 ± 0.03 kg each for home consumption. Neither cake nor manure is produced for market purpose in the area. Apart from its major contribution as a source of energy and organic fertilizer, animal dung is also put to other various minor domestic uses like plastering of walls and construction of household facilities in the studied place. The major reason for farmers to staff t diverting manure from its traditional use as the main supplier of organic fertilizer to fuel production is a lack of an alternative means for energy source. Natural forests that used to support the firewood requirement of the rural society in the past disappeared as a result of intensified deforestation in the quest for expansion cf croplands to feed the growing population. Farmers, hence, were left with no choice but to ration their daily manure harvest between fuel and fertilize) . The study indicates that farmers hold varying views on the appropriateness of whether to utilize animal dung for fuel or fertilizer: About half of the interviewed households noted that, given the current circumstances of not having an option for energy source, it is justifiable to burn manure. Eleven percent only contended manure use must be confined to fertilizer utilization while about 16 percent underlined the importance of both functions and noted sharing manure between these two uses is a judicious act. This diversion of manure from its sole use as organic fertilizer is likely to continue in the foreseeable future till alternative means for rural energy source are made available. Multipurpose tree planting, baogas technology utilization and Development in solar and wind energy use seem appealing options provided concerted effort is made to alleviate bottlenecks currently hampering their exploitation.